KEANEKARAGAMAN JENIS BURUNG DI BEBERAPA TIPE HABITAT TAMAN NASIONAL GUNUNG CIREMAI (Diversity of Bird Species at Some Habitat Type in Ciremai Mountain National Park) - Rika Sandra Dewi; Yeni A. Mulyani; Yanto Santosa (Department of Forest Resources Conservation and Ecotourism - IPB University, 2007)
Research about Diversity of bird species at some habitat type in Ciremai Mountain National Park conducted by two months (Juni-Juli 2006). This research aim to compile the list of bird species at some habitat type, comparing bird species at some habitat type and studythe use of vegetationy by the birds. To count of the birds were used Point Count with Index Point Abundance (IPA), and to analysis of thebird diversities were used Index Shannon-Wiener. Result of research were found as much 78 bird species of 26 families; 62 species of 23families were found in primary forest, 37 bird species of 18 families were found in secondary forest, 24 bird species of 13 families werefound in garden. The highest bird diversity (H’=3.90) was found in the primary forest. The strata of vegetation with the highest use on allthree habitat types were the third and fourth strata.Key words: diversity, bird, vegetation, habitat, national park